Service quality in higher education in Malaysia: perception of undergraduate students in a Malaysian public university / Siti Rapidah Omar Ali ... [et al.] - Omar Ali, Siti Rapidah; Md Shariff, Nor Alesha; Mohd Said, Nur Shafini; Mat, Khalid Amin (2018)
Service quality can be defined as the overall impression of customers towards weakness or excellence of service provided by an organization. It is a vital element that identifies the users’ satisfaction when using services whether it is as what they expected. The objective of this study is to identify the relationship between service quality and students’ satisfaction in a public university in the East Coast of Malaysia. Research framework used in this study is based on the HEDPERF model which includes academic aspect, non-academic aspect, and students’ satisfaction. A total of 265 respondents were sampled for responding with the return rate of 95.84%. Pearson correlation and multiple regression were used to analyze the relationship between academic aspect and non academic aspect towards students’ satisfaction. The results discovered that academic aspect and non academic aspects have significant relationship with students’ satisfaction. All the hypothesis tested also accepted. Academic aspect was found to be the strongest predictor of students’ satisfaction. The result of this study influences the future research in improving service quality especially in higher education institutions.